Diatom fluxes from Young Sound fjord, North-East Greenland - Mäkelä, Meri Marianne; Luostarinen, Tiia; Ribeiro, Sofia; Weckström, Kaarina; Sejr, Mikael K; Winding, Mie Hylstofte Sichlau; Heikkilä, Maija (In: Mäkelä, MM et al. (2025): Diatom and dinoflagellate cysts determination from Young Sound fjord, North-East Greenland [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982994, 2025)
Datasets collected from Young Sound fjord, Northeast Greenland, between 2013 and 2018 were analysed for diatom fuxes. An automated PPS4/3 sediment trap with an aperture of 0.05 m² was installed near the fjord entrance (74.322°N; 20.269°W) at 60-m water depth, 15 m above the seafloor as part of the Greenland Ecosystem Monitoring (GEM) programme. The rotation for the trap was set to 7 to 91 -day intervals. Diatoms were counted and identified using a Zeiss Axio Imager.A2 upright research microscope with a Plan-Apochromat 100×/1.4 oil immersion objective, phase contrast optics and a total magnification of ×1000.
Keywords: Arctic; Diatom; Dinocysts; Dinoflagellate cysts; Sediment trap; Young Sound-Greenland